Minimally Biased Nonparametric Regression and Autoregression - Timothy L. McMurry; Dimitris N. Politis (Revstat Statistical Journal, 2008)
A nonparametric regression estimator is introduced which adapts to the smoothness of the unknown function being estimated. This property allows the new estimator to automatically achieve minimal bias over a large class of locally smooth functions without changing the rate at which the variance converges. Optimal convergence rates are shown to hold for both i.i.d. data and autoregressive processes satisfying strong mixing conditions.